2017
DOI: 10.2337/db16-1291
|View full text |Cite
|
Sign up to set email alerts
|

Reestablishment of Glucose Inhibition of Glucagon Secretion in Small Pseudoislets

Abstract: Misregulated hormone secretion from the islet of Langerhans is central to the pathophysiology of diabetes. Although insulin plays a key role in glucose regulation, the importance of glucagon is increasingly acknowledged. However, the mechanisms that regulate glucagon secretion from α-cells are still unclear. We used pseudoislets reconstituted from dispersed islet cells to study α-cells with and without various indirect effects from other islet cells. Dispersed islet cells secrete aberrant levels of glucagon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 39 publications
8
41
2
Order By: Relevance
“…), human pseudoislets mirror the original intact islets well for both nonendocrine and endocrine cells. When sorted mouse beta, alpha, and delta cells were used, alpha and delta cells were incapable to form aggregates implicating beta cells are critical for the formation of pseudoislets (Reissaus and Piston ). Although it remains to be determined whether beta cell drives formation of pseudoislets in humans, our data indicate that the formation of pseudoislets have little selectivity in inclusion or exclusion of cell types to be incorporated for both endocrine and nonendocrine cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), human pseudoislets mirror the original intact islets well for both nonendocrine and endocrine cells. When sorted mouse beta, alpha, and delta cells were used, alpha and delta cells were incapable to form aggregates implicating beta cells are critical for the formation of pseudoislets (Reissaus and Piston ). Although it remains to be determined whether beta cell drives formation of pseudoislets in humans, our data indicate that the formation of pseudoislets have little selectivity in inclusion or exclusion of cell types to be incorporated for both endocrine and nonendocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…). As the three‐dimensional structure of pancreatic islets supports viability and function of beta cells through cell‐cell and cell‐matrix communications (Rutter and Hodson ; Arous and Wehrle‐Haller ; Reissaus and Piston ; Briant et al. ), it is critical to address beta cell pathophysiology in pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fractionating the differentiated pancreatic organoids into individual cells for the purpose of isolating only beta cells would disrupt the islet architecture generated in the dish that is sought to recapitulate in vivo development. To this extent, it has been demonstrated that isolated pancreatic beta cells underperform those in intact islets in insulin secretion response [54][55][56], indicating that establishment of the strategic cell-cell and cell-matrix contacts by beta cells with the islet is rather crucial to conferring its functional properties. In contrast, isolation of pure beta cells generated within the hPSC-derived pancreatic organoid and their re-aggregation to establish beta cell-beta cell contact improved their metabolic maturation and glucose-responsiveness [20].…”
Section: Isolation Of Pure Hpsc-derived Pancreatic Lineagesmentioning
confidence: 99%
“…Pancreatic islet architecture with appropriate distribution of different endocrine cell types has been shown to contribute towards beta cell functionality and glucose responsiveness. Resonating from the findings that beta cells within an intact islet are more precise in their secretory and calcium response to elevated glucose levels than those in dissociated or dispersed islets [54][55][56], it is important to consider that intra-islet cell-cell communication between beta cells and other endocrine cells as well as amongst different subpopulations of beta cells is crucial for paracrine signaling and enhanced electrical coupling [59][60][61].…”
Section: Intra-islet Cell Contact and Communication For Functional Pementioning
confidence: 99%